Addressing Learning Difficulties in Junior High School Physics Education: Insights for Curriculum Development and Teaching Strategies - Shrestha, Polanski Snyder; Perlman, Tancredi Thorne; Shaver, Scuka Rousseau (Jurnal Ilmu Pendidikan dan Humaniora, 2023)
This research delves into the intricate analysis of students' learning difficulties in comprehending physics material at the junior high school level. Through a comprehensive investigation involving mixed-methods research, encompassing both qualitative and quantitative approaches, the study sought to identify prevalent misconceptions, cognitive barriers, and socio-economic factors influencing students' understanding of fundamental physics concepts. The research illuminated the pervasive misconceptions encountered by students, particularly in areas related to force and motion, energy conservation, wave behavior, electricity, and abstract concepts in quantum physics. Cognitive barriers, stemming from the abstract nature of physics principles and the incongruence with everyday experiences, posed significant challenges for students in comprehending these complex concepts. Insights from this research emphasized the critical need for innovative pedagogical approaches, integrated with real-world applications, to bridge the gap between abstract scientific principles and students' experiences. Curriculum reforms aimed at contextualizing physics concepts and accommodating diverse learning styles were identified as crucial for fostering an engaging and effective learning environment. Moreover, the study shed light on socio-economic disparities that influenced students' readiness and access to resources, advocating for equity in educational support and opportunities. The findings from this research have far-reaching implications, calling for systemic changes in teaching methodologies, curriculum design, and policy initiatives to enhance the learning experience in physics education. The research serves as a beacon for educators, curriculum developers, and policymakers, guiding them toward transformative changes essential for nurturing a generation of students equipped with a deeper understanding of fundamental scientific principles in physics.